PEMANFAATAN SABUT KELAPA DAN KAYU BAKAU (Rhizophora sp.) DALAM PEMBUATAN BRIKET SEBAGAI RANCANGAN MODUL PADA MATERI BIOTEKNOLOGI SMA - Nurahma Dini; Imam Mahadi; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the composition of the mixture of coconut coir and mangrove wood with the best variation of briquette pressure and produce a learning module design on high school biotechnology class XII material. This research was conducted at the Biology Education Laboratory of FKIP, Production Laboratory, and Energy Conversion in Mechanical Engineering, Riau University. This research lasted for 3 months starting from March - May 2019. This research was conducted in 2 stages: the first stage: the experiment of utilizing coconut fiber and mangrove wood in briquette making and the second stage: the design of biotechnology learning modules in high school. This study used an experimental method with a factorial completely randomized design of 5 x 3 consisting of 5 types of treatment in the composition of coconut coir and mangrove wood composition and 3 types of treatment on briquette pressures with 3 replications each. The parameters measured in this study are water content, ash content and heating value. The results of this study produced the briquettes with the best combination found in the A3B3 treatment, namely the composition of 25% coconut fiber and 75% mangrove wood with the use of briquette pressure of 150 kg / cm3. Based on the analysis of the potential of the research results can be used as a module design learning materials biotechnology class XII high school.Key Words: Coconut coir, mangrove wood, briquettes, briquette pressure, module